2009
DOI: 10.1590/s0102-311x2009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychological stress on blood pressure increase: a meta-analysis of cohort studies

Abstract: Studies have suggested that chronic exposure to stress may have an influence on increased blood pressure. A systematic review followed by a meta-analysis was conducted aiming to assess the effect of psychological stress on blood pressure increase. Research was mainly conducted in Ingenta, Psycinfo, PubMed, Scopus and Web of Science. Inclusion criteria were: published in any language; from January 1970 to December 2006; prospective cohort design; adults; main exposure psychological/emotional stress; outcome art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 37 publications
2
79
0
12
Order By: Relevance
“…A meta-analysis [21] of six cohort studies involving 34,556 volunteers, performed in order to analyze the effect of psychological stress on arterial blood pressure increase, showed that individuals with a greater reaction to stressor tasks were more likely to present an increase in arterial blood pressure when compared to those with a lower reaction (OR = 1.21; 95%CI: 1.14-1.28; p < .001). Although the study data showed a relatively modest magnitude of effect, the findings suggest the importance of controlling psychological stress as part of a non-drug treatment of systemic arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis [21] of six cohort studies involving 34,556 volunteers, performed in order to analyze the effect of psychological stress on arterial blood pressure increase, showed that individuals with a greater reaction to stressor tasks were more likely to present an increase in arterial blood pressure when compared to those with a lower reaction (OR = 1.21; 95%CI: 1.14-1.28; p < .001). Although the study data showed a relatively modest magnitude of effect, the findings suggest the importance of controlling psychological stress as part of a non-drug treatment of systemic arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed the increases in SBP and DBP to the mental stress task were substantial and significant (57.61mmHg and 38.31mmHg; p<0.001) [24]. A meta analysis of cohort studies showed that individuals who had stronger responses to stressor tasks were 21% more likely to develop blood pressure increase when compared to those with less strong responses in adult aged between 18 and 64 years [25]. Administration of stress with air pressure 5 times a week, each 30 minutes, could increases the SBP 13 mmHg [26] with light exposure 3 times a week each 30 minutes increases SBP significantly [27], and with restraint a week increase 49.5 mmHg [28].…”
Section: Resultsmentioning
confidence: 95%
“…Results showed individuals who had stronger responses to stressor task were 21% more likely to develop blood pressure increase when compared to those with less strong response (OR: 1.21; 95% CL: 1.14 -1.28; p<0.001). [15] Regarding coexisting diseases, most of the hypertensives were found to have both diabetes mellitus and dyslipidaemia, which was statistically significant. Among hypertensives, 45% were diabetic compared to 21.6% among non-hypertensives.…”
Section: Discussionmentioning
confidence: 93%